Answer:
0
Step-by-step explanation:
12-(-4)(-3)
-3 x -4 = 12
12 - 12= 0
F(x) = 2x - 4
f(2 ≤ x) = 2(2 ≤ x) - 4
f(x ≥ 2) = 2(x ≥ 2) - 4
f(x ≥ 2) = 2(x) ≥ 2(2) - 4
f(x ≥ 2) = 2x ≥ 4 - 4
f(x ≥ 2) = 2x ≥ 0
f(x ≥ 2) = x ≥ 0
f(x) = 2x - 4
f(x ≤ 6) = 2(x ≤ 6) - 4
f(x ≤ 6) = 2(x) ≤ 2(6) - 4
f(x ≤ 6) = 2x ≤ 12 - 4
f(x ≤ 6) = 2x ≤ 8
f(x ≤ 6) = x ≤ 4
<u>Answer</u>
C. 39.71
<u>Explanation</u>
33 = p - 6.71
The first step is to make the like terms to be on the same side.
Add 6.71 on both sides of the eqution
33 + 6.71 = p - 6.71 + 6.71
39.71 = p
∴ p = 39.71
Answer:
h(2)=6
Step-by-step explanation:
just plug in 2 where you have an x, and you’d have 2 + 6, which equals 6
it will take to fill a 10 liter container= 33.3 hours